Wine as a cultural product: Symbolic capital and price formation in the wine field - Jens Beckert; Jörg Rössel; Patrick Schenk (Max Planck Institute for the Study of Societies, 2014)
Understanding the valuation of goods in markets has become one of the key topics in economic sociology in recent years. Especially in markets for goods that are valued for their aesthetic qualities, the ascription of value appears to be a complex social process because product quality is highly uncertain. The wine market is an extraordinary example because most consumers and even experts are not able to differentiate between wines based on objective sensory characteristics and cannot rank wines in blind tastings according to their price. Our premise is that assessed quality differences cannot be explained by the sensual qualities of the wine. Instead, we explain variations in valuation by social processes in which quality is constructed and contested. To do so we make use of Bourdieu's field theoretical perspective, which is strongly supported in our empirical analysis of the German wine field. It shows that his model of the structure of fields has considerable power in explaining price differentiation between wineries and that the orientation of consumers towards different segments of the field is based on class hierarchy. – – Die Untersuchung der Grundlagen des Werts von Gütern ist gegenwärtig eines der zentralen Themen der Wirtschaftssoziologie. Besonders in Märkten für Güter, deren Nutzen vornehmlich in ästhetischen Qualitäten besteht, ist die Konstruktion von Wert ein komplexer sozialer Prozess, da Produktqualität hochgradig ungewiss ist. Der Weinmarkt ist hierfür ein besonders gutes Beispiel. Die meisten Konsumenten und sogar Experten sind nicht in der Lage, Wein an seinen sensorischen Qualitäten zu unterscheiden, und können einen Wein in Blindverkostungen auch nicht in eine Preisskala einordnen. Unser Ausgangspunkt ist die Annahme, dass wahrgenommene Qualitätsunterschiede nicht durch die sensorischen Qualitäten des Weins erklärt werden können. Stattdessen erklären wir Wertunterschiede durch soziale Prozesse, in denen Qualität konstruiert und kontrovers diskutiert wird. Dafür nutzen wir Bourdieus Feldtheorie, die in der empirischen Analyse des deutschen Weinfeldes starke Unterstützung findet. Es zeigt sich, dass sein Modell der Struktur des Weinfeldes erhebliche Erklärungskraft bei der Erklärung von Preisunterschieden zwischen Weingütern hat und dass die Orientierung der Konsumenten auf je unterschiedliche Segmente des Feldes in Klassenhierarchien begründet liegt.
Keywords: 300